Construction of Malaysian Chineseness through biometaphors in Malaysian Chinese literature in English - Chong, Seng Tong (2015)
This thesis examines the interaction between human and nonhuman (animals,plants and abiotic elements) from a biologically oriented perspective. It reads contemporary Malaysian literature in English written by Malaysian Chinese authors. Reading these bodies of texts from a biological perspective challenges the way we think about human and nonhuman interaction, specifically in relation to Malaysian Chinese and their cultures. Drawing various scientific rubrics from biological science as the theoretical frameworks can provide insightful reading and findings. With Conceptual Metaphor Theory as its methodological framework, this thesis examines the biophilic ideological construct of “Malaysian Chineseness” revealed in the works of Tan Twan Eng, Ho Thean Fook, Tash Aw, Khoo Kheng Har and Chong Seck Chim. The key findings indicate that the Malaysian Chinese use very specific to universal biometaphors in ideas construction. In addition, the Malaysian Chineseness is biophilic, which suggests the existence of harmony and peace with the environment as well as with the influence of Malaysian Chinese religion. Chapter one brings together many theoretical and current concerns that provide an impetus for the onset of this thesis. It sets out as a starting point for the research journey. Chapter two discusses literature on biophilia hypothesis, a theoretical framework from the biological science in relation to Malaysian Chinese. It also discusses the biological reading of literary texts within the broader scope of Malaysian Chineseness. Chapter three explains the methodological framework with step by step procedures, in detail. The procedure is divided into metaphor identification, metaphor interpretation and metaphor explanation. Chapter four is devoted to the analysis and discussion of the research pertaining to linking biometaphors, biophilia and Malaysian Chineseness. Lastly, chapter five concludes the entire research by revealing the idea of Malaysian Chineseness.